Importance Of Leguminous Crops (In the Example Of "Genetic-1" Variety of Soya Bean) In Increasing Soil Fertility - G.N. Jorakulov; G.E. Kosimova (Zien Journals, 2023)
This article provides information on the importance of soybean from leguminous crops in increasing soil fertility. The "Genetic-1" soybean variety was used in the research. According to the results, these three types of soybeans are highly effective in increasing soil fertility.
Keywords: Soil; soy; productivity; Genetic